Experimental Investigations on Applicability of Eco Friendly, Green and Sustainable Farm/Fish Pond Liner As A Component for Water Storage System - Nagashree B (International Journal of Sustainable Construction Engineering and Technology, 2023)
It is a well-known fact that in most of the regions, rainfall shall not meet the crop water requirements. Hence it is very much necessary to have water storage system to meet the water demand. The rate of seepage is considered to be high in case of earth ponds. By considering this, there is an urgent requirement to reduce the seepage in the water storage system and increase the irrigation efficiency. This research studies is based on minimizing the seepage in the ponds by providing a liner material, which is eco-friendly, sustainable, economic with good serviceability.  In this experiment the sodium based salts are used in combination with Bauxite Mine Residue (BMR) and Ordinary Portland Cement (OPC) as binder materials for the liner system to decrease the seepage. Three proportions of the binder were used in the study viz. BMR: OPC as 80:20. Sodium carbonate (SC) was used in the proportion of 0%, 2% 4%, 6% 8% 10% and 12% by weight of binder. SEM analysis, pH permeability and compaction tests were conducted to determine the performance of the liner material. Results showed that the binder ratio of BMR: OPC with ratio 80:20 with sodium carbonate content 10% showed the better results with more reduction in seepage, maximum reduction in permeability. Hence the present studies prove that the produced pond liner shall reduce seepage effectively and have more serviceability compared to plastic liners.